Employability of Irish Nutrition Science Graduates–A Qualitative Exploration of Graduates' Experiences and Perceptions. - O'Donovan, Sarah; Ryan, Lisa (Journal of Human Nutrition & Dietetics, 2025)
Background: Nutrition science and nutrition‐related programme graduates possess extensive knowledge, practical skills, and effective communication, but the transition from academic training to professional practice can be challenging. The study aimed to explore the factors influencing employability of Irish nutrition graduates. Methods: In‐depth semi‐structured, recorded interviews were conducted with 42 nutrition graduates from across nine universities in Ireland who had completed a nutrition science degree between 2015 and 2021. Interpretivism guided this study, which endeavoured to co‐construct meaning with participants. Transcribed interviews were narratively analysed, whereby data were coded, categorised and discussed by all authors. The data were further mapped against CareerEDGE model by deductively coding against the model components (experience, degree, generic skills, emotional intelligence, career development learning, and reflection and evaluation). Results: All components of the CareerEDGE model were identified in the data. Experience, degree, and generic skills were recognised as the components with the greatest impact on job outcomes and performance. All participants referenced both work and life experience as an influential factor in their journey to employment, providing exposure to different workplace environments and opportunities for skills development. Conclusion: Irish nutrition science graduates acknowledged the significance of experience, degree knowledge, and generic skills in employability. Further research is needed to improve career development opportunities and support, emotional intelligence, and resilience in nutrition science education. Summary: Experience, degree knowledge, and generic skills were regarded as the primary factors influencing employability and performance.Work and life experiences were reported as essential for skill development and career preparedness.Increased emphasis on career development, emotional intelligence, and resilience in education could better support graduates for the modern workforce.